Physiological Characterization and Genetic Diversity Assessment of the Rhizobial Populations Inhabiting Gliricidia sepium in selected Locations of Ampara District, Sri Lanka - P.W.I. Nawanjana; Sanath Rajapakse (Journal of Agricultural Sciences, 2018)
Purpose: Gliricidia sepium is a wide spread multipurpose legume plant which is effective in nitrogen fixation and host to many Rhizobial strains. However, few studies have been carried out to identify and characterize the Rhizobial populations inhabiting G. sepium in Sri Lanka. The main objective of this study was to isolate and identify the stress tolerant Rhizobial strains in G. sepium.